Local climate change reporting in coastal cities: Selsey (UK), Santos (Brazil) and Broward County (USA) - Prado Gutierrez, Eduardo (Ámbitos. Revista Internacional de Comunicación, 2022)
Climate change media coverage has been criticized for giving voice to denialist sources and for its detachment from local and individual experiences, emphasizing catastrophic and global impacts. This article seeks to understand the potential connection between regional media and local climate change meanings through analysis of the journalistic output in regional newspapers in three vulnerable coastal cities that have presented developments regarding local climate governance: Santos (Brazil), Selsey (UK) and Broward County (USA). The vehicles analyzed in each of the cities are A Tribuna de Santos, The Chichester Observer and The Sun Sentinel, respectively. The method used is quantitative content analysis, focusing on the appearance of sources and recurring local issues and symbols on the climate change coverage of these regional vehicles. As a result, there are interesting differences of sources and issues between regions, with beaches and shoreline neighborhoods condensing the attention over climate impacts in Santos and Broward; and the dangers of real estate development in low- lying land and natural reserves occupying the center of attention in Selsey. Among the three locations, only Broward presented a significant degree of climate denialist sources.